2004
DOI: 10.1007/s00167-003-0393-4
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of chondral lesions of the knee joint: can MRI replace arthroscopy?

Abstract: The role of magnetic resonance tomography (MRI) for the diagnosis of chondral lesions of the knee joint is still unclear. The sensitivity of the method ranges from 15% to 96%. The scope of our daily experiences showed that there were considerable deviations between the tomographical and arthroscopical results, which vary from the results of experimental studies. Therefore we have conducted a prospective study to investigate the question of how MRI can replace arthroscopy (ASC) in the diagnosis of cartilage dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
65
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(70 citation statements)
references
References 29 publications
5
65
0
Order By: Relevance
“…Our low detection rate of chondral lesions by MRI support a previous report suggesting these lesions are difficult to observe in the ankle [26] and in the knee using conventional MRI techniques [5,13,14,22]. Although meniscus and ligament injuries are easily imaged, arthroscopy is required to see articular cartilage injuries in the knee [5,14].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Our low detection rate of chondral lesions by MRI support a previous report suggesting these lesions are difficult to observe in the ankle [26] and in the knee using conventional MRI techniques [5,13,14,22]. Although meniscus and ligament injuries are easily imaged, arthroscopy is required to see articular cartilage injuries in the knee [5,14].…”
Section: Discussionsupporting
confidence: 81%
“…Although meniscus and ligament injuries are easily imaged, arthroscopy is required to see articular cartilage injuries in the knee [5,14]. Also, almost all lesions missed on MRI in our study were full thickness and warranted microfracture, but the lesions were not large or deep.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…22 Four years later, another independent study concluded that MRI is only reliable at excluding such lesions, but that the arthroscopy is still the preferable method for a secure diagnosis. 23 According to all data that were collected, it seems reasonable to admit that we have, at present, not enough information to determine in what cases the MRI abnormality actually reveals a pathology that is enough to justify the interruption of the treadmill training or even justify specific treatment (surgical or not). After all, it has already been proven that the training program can bring positive results for the cardio-respiratory system.…”
Section: Discussionmentioning
confidence: 99%
“…The role of MRI for the diagnosis of chondral lesions of the knee joint is still unclear, and the sensitivity of the method ranges from 15 to 96 percent (Friemert et al, 2003). In a prospective study by Friemert et al (2003) of how MRI can replace arthroscopy in the routine diagnosis of cartilage damage, they found that the MRI cartilage specific sequences have a sensitivity of 33 percent and specificity of 99 percent and positive and negative prediction values of 75 and 98 percent respectively.…”
Section: Can Mri Replace Arthroscopy In Diagnosis?mentioning
confidence: 99%